2017
DOI: 10.4196/kjpp.2017.21.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of vascular smooth muscle phenotype by cross-regulation of krüppel-like factors

Abstract: Regulation of vascular smooth muscle cell (VSMC) phenotype plays an essential role in many cardiovascular diseases. In the present study, we provide evidence that krüppel-like factor 8 (KLF8) is essential for tumor necrosis factor α (TNFα)-induced phenotypic conversion of VSMC obtained from thoracic aorta from 4-week-old SD rats. Stimulation of the contractile phenotype of VSMCs with TNFα significantly reduced the VSMC marker gene expression and KLF8. The gene expression of KLF8 was blocked by TNFα stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…Primary VSMCs were isolated from SD rat thoracic aortas, as described previously (19). In brief, animals were sacrificed by intraperitoneal injection of 2% pentobarbital sodium (50 mg/kg; Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) and perfused with saline for 5 min.…”
Section: Primary Culture Identification and Transfection Of Vsmcsmentioning
confidence: 99%
“…Primary VSMCs were isolated from SD rat thoracic aortas, as described previously (19). In brief, animals were sacrificed by intraperitoneal injection of 2% pentobarbital sodium (50 mg/kg; Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) and perfused with saline for 5 min.…”
Section: Primary Culture Identification and Transfection Of Vsmcsmentioning
confidence: 99%
“…The cross-regulation of KLF8 and KLF5 is also detected in the TNF-α-induced phenotypic switch of VSMCs. Suppressed KLF8 expression and increased KLF5 expression contribute to the reverse of contractile phenotype ( Ha et al, 2017 ). In vein graft, VSMC phenotype switch is a significant component of pathological adaption.…”
Section: Roles Of Klf5 In Vascular Remodelingmentioning
confidence: 99%
“…In addition, we found the expression trend among different groups of KLF5 was consistent when b-actin was regarded as the housekeeping gene (Supplementary Figure 2B). A molecule present downstream of KLF5, myocardin, is considered a key modulator for VSMC differentiation marker genes (10). A previous study has demonstrated that KLF5 negatively regulates myocardin (21).…”
Section: Mir-9 Alleviates the Phenotypic Conversion Of High Glucose-induced Vsmcs By Modulating The Expression Of Klf5 And Myocardinmentioning
confidence: 99%
“…KLF5, a member of the family of Kruppel-like factors, belongs to a group of transcription factors containing zinc finger domains, and serves as a transcriptional activator or repressor, regulating a variety of physiological processes, including differentiation, development, and proliferation (7,8). However, KLF5 is also modulated by a variety of biological mechanisms, including microRNA, and other transcriptional factors (9)(10)(11). Previous studies have demonstrated that KLF5 might contribute to VSMC dedifferentiation and synthetic phenotype change in balloon-injured artery and platelet-derived growth factor (PDGF)-stimulated VSMCs (9).…”
Section: Introductionmentioning
confidence: 99%